A new macrocyclic ligand as a turn-on fluorescent chemosensor for the recognition of Pb2+ ions. (26th September 2017) - Azadbakht, Reza; Hakimi, Mohammad; Khanabadi, Javad; Amiri Rudbari, Hadi
Abstract : The chemosensor L has a detection limit of 9.63 nM for Pb 2+ in an acetonitrile/H2 O (9 : 1, v/v) mixture. Abstract : A new asymmetric macrocyclic ligand was synthesized and characterized by NMR studies, X-ray diffraction and mass spectroscopy. Based on the photoinduced electron transfer (PET) fluorescence enhancement mechanism, the ligand has been successfully used for the efficient detection of Pb 2+ in aqueous buffer media (pH 7.4). The detection limit of Pb 2+ is up to 9.63 × 10 −10 M.